Peningkatan Keaktifan, Sikap Percaya Diri, dan Hasil Belajar IPS melalui Model Pembelajaran Tipe STAD - Nova Ariyanti; Sunarti Sunarti (UM Purwokerto Press, 2022)
This study aims to know increasin the activeness, self-confidence, and learning outcomes of students in social studies learning through the application of the STAD type learning model. This research was conducted at SD Negeri Winongkidul. The subjects in this study were sixth grade students of SD Winongkidul. This type of research is classroom action research. Data collection techniques in this study used questionnaires and observation sheets. The data analysis technique used descriptive quantitative with percentages. The results showed that 1) Increasing the activeness of students in social studies learning through the application of the STAD model by the pre-cycle at 13 students (54.17%) increased in the first cycle to 17 students (70.84) and the second cycle to 21 students (87.5%). 2) Increased self-confidence of students in social studies learning through the application of the STAD type learning model in the pre-cycle 14 students (58.33%) increased in the first cycle to 19 students (79.17) and in Cycle II to 23 students (95.83%) 3) Improving student learning outcomes in social studies learning through the application of the STAD model in the pre-cycle 12 students (50%), increased in the first cycle to 16 students (66.67%) and in the second cycle increased to 22 students (91.67%).